2008
DOI: 10.1071/ah080265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hospital volunteer program in rural Australia

Abstract: A voluntary survey questionnaire that assessed experience with and perception of the volunteering program was mailed to 62 current and 9 former volunteers and 47 staff members of Latrobe Regional Hospital (LRH). Sixty-one completed questionnaires were returned. The nature of hospital work attracted volunteers (57%) and most volunteers felt oriented to the hospital, supervised and supported. The volunteers enjoyed working with patients and felt they contributed to better services and staff and patient support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is predicted that the need for volunteers, especially in rural areas in Australia will continue to grow [13], and further that hospital administrators need to recognise this rich resource. Like this study, previous studies have found that the utilisation of volunteers has a positive im-pact on patient quality of care and staff time management [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is predicted that the need for volunteers, especially in rural areas in Australia will continue to grow [13], and further that hospital administrators need to recognise this rich resource. Like this study, previous studies have found that the utilisation of volunteers has a positive im-pact on patient quality of care and staff time management [13].…”
Section: Discussionmentioning
confidence: 99%
“…Volunteers are defined as people who perform an activity in which time is given freely to benefit another person, cause or group [12]. While there are over six million volunteers in Australia, a past survey found that only 12% of these were in the health sector [13]. Given the decreasing resources in the health sector, volunteers are increasingly being utilised to play a crucial role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation